2007
DOI: 10.1017/s1049023x0000529x
|View full text |Cite
|
Sign up to set email alerts
|

Population Psychiatric Medication Prescription Rates following a Terrorist Attack

Abstract: Introduction:While several population-based studies have documented behavioral health disturbances following terrorist attacks, a number of mental health service utilization analyses present conflicting conclusions.Purpose:The purpose of this study was to determine if mental health service utilization increased following a terrorist attack by assessing changes in psychoactive drug prescription rates.Methods:The rate of selective serotonin reuptake inhibitor (SSRI) prescriptions was measured among New York Stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
38
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 30 publications
6
38
1
Order By: Relevance
“…While we, among others, have put large administrative health datasets to public health use, 37, 38 administrative data are a blunt instrument to assess possibly subtle neurocognitive outcomes. There will, inevitably, be measurement error, particularly in diagnoses which are abstracted by nonclinical personnel and must conform to insurance billing standards.…”
Section: Discussionmentioning
confidence: 99%
“…While we, among others, have put large administrative health datasets to public health use, 37, 38 administrative data are a blunt instrument to assess possibly subtle neurocognitive outcomes. There will, inevitably, be measurement error, particularly in diagnoses which are abstracted by nonclinical personnel and must conform to insurance billing standards.…”
Section: Discussionmentioning
confidence: 99%
“…In the presence of a functioning healthcare system, psychotropic use in this context can be regarded as an indirect measure of community psychiatric morbidity (Usher et al, 2012). Study designs include phone surveys of affected individuals addressing medication use (Boscarino et al, 2003) and pharmaco-epidemiological studies extracting prescribing medication rates for populations (Rossi et al, 2011) or sub-populations such as insurance holders (DiMaggio et al, 2007). The most consistent findings are short-term increases in prescribing of sedating medication (benzodiazepines and antipsychotics).…”
Section: Introductionmentioning
confidence: 99%
“…16,17 The two latter conditions can lead to the prescription of psychotropic drugs in an attempt to relieve the symptoms of distress, particularly the symptoms of acute stress disorder (ASD) and PTSD. 7,16,19 All three studies reported an increase in the prescription of psychotropic drugs, and hence assumed an increased usage of drugs used to treat psychological distress by members of the community. 7,16,19 All three studies reported an increase in the prescription of psychotropic drugs, and hence assumed an increased usage of drugs used to treat psychological distress by members of the community.…”
Section: Introductionmentioning
confidence: 99%
“…7,18 To date, only three studies have attempted to determine the extent of psychological distress in a community by measuring the changes in psychotropic drug prescription rates. The first study used a telephone survey, 19 the second measured the use of a specific group of antidepressant drugs only, 16 and the most recent study used a pharmaco-epidemiological approach to compare the usage of antidepressant and antipsychotic drugs after the event with the same time period in the previous year. The first study used a telephone survey, 19 the second measured the use of a specific group of antidepressant drugs only, 16 and the most recent study used a pharmaco-epidemiological approach to compare the usage of antidepressant and antipsychotic drugs after the event with the same time period in the previous year.…”
Section: Introductionmentioning
confidence: 99%